2020
DOI: 10.3389/fmars.2020.00127
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis Reveals Reduced Coral Calcification Under Projected Ocean Warming but Not Under Acidification Across the Caribbean Sea

Abstract: Ocean acidification and warming are two of the many threats to coral reefs worldwide, and Caribbean reef-building corals are especially vulnerable. However, even within the Caribbean, experimental acidification and warming studies reveal a wide array of coral calcification responses across reef systems and among species, complicating efforts to predict how corals will respond to these global-scale stressors. We conducted a meta-analysis to investigate the calcification responses of Caribbean corals to experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 60 publications
0
24
0
Order By: Relevance
“…The effect of ocean acidification (OA) on corals and particularly on calcification rates has been the focus of intense debate (Bove et al., 2020; Mollica et al., 2018). Although some studies have identified internal upregulation of pH as an acclimatory mechanism for coral to overcome the effect of OA (McCulloch et al., 2012), recent laboratory studies have challenged the magnitude of resistance that this mechanism may provide (Comeau et al., 2019).…”
Section: Sensitivity Of Tabular Acropora To Different Disturbancesmentioning
confidence: 99%
“…The effect of ocean acidification (OA) on corals and particularly on calcification rates has been the focus of intense debate (Bove et al., 2020; Mollica et al., 2018). Although some studies have identified internal upregulation of pH as an acclimatory mechanism for coral to overcome the effect of OA (McCulloch et al., 2012), recent laboratory studies have challenged the magnitude of resistance that this mechanism may provide (Comeau et al., 2019).…”
Section: Sensitivity Of Tabular Acropora To Different Disturbancesmentioning
confidence: 99%
“…Similarly, when all previous sitespecific models that use physicochemical parameters to predict G net were compiled, the only model to significantly correlate with global G net observations relied on temperature alone 42,67 . In general, increasing temperatures increase coral growth until a thermal threshold is reached 29 . The magnitude of this effect can be dependent on species, location or latitude 56,91 .…”
Section: Discussionmentioning
confidence: 99%
“…Higher rates of G net tend to indicate reefs with higher coral cover 9,21,22 , and ecosystems which have not been impacted by significant stressors [23][24][25][26] , whereas declining and net-dissolving calcification rates indicate stressed corals 16,18,27 or ecosystems which have little to no live corals 25,28 . Therefore, G net and P net are increasingly used as proxies for coral reef ecosystem health 10,29,30 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Research over the last 20 years to understand the impact of ocean acidification [84] has produced variable results [90,91]. Species that can maintain calcium carbonate saturation levels in their internal calcifying sites may be less affected by changes in seawater pH.…”
Section: The Ocean Carbon Cycle and Acidificationmentioning
confidence: 99%